EXPLORING THE ROLE OF CORPORATE GOVERNANCE IN ENHANCING THE TRANSPARENCY OF BANKING INSTITUTIONS - Aripin, Zaenal; Susanto, Bambang; Agusiady, Ricky (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background:Corporate governance is critical for banking stability, with governance failures exposed as root causes of institutional collapse in financial crises. Aims:This study explores corporate governance's role in enhancing transparency and performance of banking institutions. Research Method:Using mixed-methods, we examined governance structures across 30 banks in diverse regulatory environments, analyzing governance metrics, performance indicators, and stakeholder interviews. Results and Conclusion:Banks with independent boards showed 15% higher ROE and 22% lower NPL ratios. Transparency correlated strongly with market valuations. Effectiveness varies across contexts with cultural and regulatory moderators. Contribution:The research elucidates mechanisms through which governance influences banking performance and provides practical frameworks for strengthening governance systems.